Performance evaluation and system design of 6G cooperative integrated sensing and communication technology - GAO Peng; ZHOU Feifei; WANG Qixing; LIAN Lixiang; YU Jinpei; MA Tao (Dianxin kexue)
As a promising technique for 6G integrated sensing and communication, cooperative integrated sensing and communication (CoISAC) technology harnesses additional sensing information from various network nodes to overcome challenges of ISAC systems such as low sensing accuracy, non-line-of-sight path scenario, and limited sensing range. The current status of CoISAC technology was summarized and analyzed. A novel performance metric and two cooperative approaches were proposed. The challenges faced by CoISAC technology were analyzed, and the future development trend of CoISAC technology was forecasted.